Pathogenetic kardiolin in patients with coronary artery disease with concomitant patology of diabetes - Halysh, I. V.; Petryshen, O. I.; Hrytsiuk, M. I.; Vivsyannyk, V. V.; Chornenka, Zh. A. (Journal of Education, Health and Sport, 2020)
The paper studied the basic pathogenic mechanisms in the development of coronary heart disease and type 2 diabetes, defined the common aspects of the etiology and clinical manifestations of similarities. The main pathophysiological characteristics and causes of coronary heart disease when accompanied by type 2 diabetes. Based on specific data pathogenesis expediency kardiolini use as auxiliary phytotherapeutic drug in patients with coronary artery disease with co-morbidities of diabetes. Also, the influence of the main components of the drug on humans. Kardiolini - complex herbal preparation, which is characterized sedation, isotropic positive and negative chronotropic effect, improve cerebral and coronary blood flow, preventing thrombosis, lowering lipids, cholesterol and triglyceride blood, that the impact on common pathogenic mechanisms of coronary heart disease and type 2 diabetes.